2015
DOI: 10.1128/iai.03136-14
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clostridium perfringens TpeL Toxin Gene Carriage, Production, Cytotoxic Contributions, and Trypsin Sensitivity

Abstract: Large clostridial toxins (LCTs) are produced by at least four pathogenic clostridial species, and several LCTs are proven pivotal virulence factors for both human and veterinary diseases. TpeL is a recently identified LCT produced by Clostridium perfringens that has received relatively limited study. In response, the current study surveyed carriage of the tpeL gene among different C. perfringens strains, detecting this toxin gene in some type A, B, and C strains but not in any type D or E strains. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…While the above evidence supports tpe L expression during sporulation, TpeL production by C. perfringens isolates during vegetative growth has also been reported (98, 99). Furthermore, those studies found repression of TpeL production mediated by glucose in a similar manner to LCT production by C. difficile .…”
Section: Sporulation-associated Toxinsmentioning
confidence: 75%
“…While the above evidence supports tpe L expression during sporulation, TpeL production by C. perfringens isolates during vegetative growth has also been reported (98, 99). Furthermore, those studies found repression of TpeL production mediated by glucose in a similar manner to LCT production by C. difficile .…”
Section: Sporulation-associated Toxinsmentioning
confidence: 75%
“…However, previous studies (37,(40)(41)(42) have shown that mutations from group II introns inserted in the sense orientation can be partially reversed at the mRNA level by growth at 30°C in the presence of an LtrA-encoding plasmid, such as pJIR750ccpAi, with the frequency of this reversion varying for different intron insertions. Therefore, pJIR750ccpAi was reintroduced into strain ccpAko, creating strain ccpArev, in order for LtrA to remove by splicing under permissive 30°C conditions, the sense-oriented intron from some ccpA mRNA, thus restoring a functional ccpA transcript and CcpA production.…”
Section: Resultsmentioning
confidence: 99%
“…A large clostridial glucosylating cytotoxin referred to as TpeL, and homologous to TcdA and TcdB from C. difficile, also appears to have a role in the pathogenesis of NE (Chen and McClane 2015). TpeL is encoded on a conjugative plasmid (Chen and McClane 2015) and binds to LDL receptor-related protein 1 in the target cells (Schorch et al 2014).…”
Section: Perfringens Tpelmentioning
confidence: 99%
“…A large clostridial glucosylating cytotoxin referred to as TpeL, and homologous to TcdA and TcdB from C. difficile, also appears to have a role in the pathogenesis of NE (Chen and McClane 2015). TpeL is encoded on a conjugative plasmid (Chen and McClane 2015) and binds to LDL receptor-related protein 1 in the target cells (Schorch et al 2014). Experimental infections with C. perfringens TpeL-positive strains in broilers induce more severe intestinal lesions and cause NE, with a more rapid course and higher fatality rate than those strains lacking this cytotoxin (Coursodon et al 2012).…”
Section: Perfringens Tpelmentioning
confidence: 99%